JHEA, Volume 15, n°2, 2017 - Full Issue - system, journal (Journal of Higher Education in Africa, 2021)
Contents Positioning Universities as Engines of Innovation for Sustainable Development and Transformation Paul Tiyambe Zeleza .................................................1 Enhancing Doctoral Supervision Practices in Africa: Reflection on the CARTA Approach Manderson, Göran Bondjers, Chimaraoke Izugbara, Donald C. Cole, Omar Egesah, Alex Ezeh, Sharon Fonn ............................23 Performative Injunctions in the Higher Education Body: The Discursive Career of Research Capacity Development in a South African University Faculty of Education Aslam Fataar .......................................41 Implications of Social Media on Student Activism: The South African Experience in a Digital Age Mthokozisi Emmanuel Ntuli & Damtew Teferra ..................................63 Analysing South Africa’s Soft Power in Africa through the Knowledge Diplomacy of Higher Education Olusola Ogunnubi & Lester Brian Shawa ...................................81 Effet des caractéristiques pré-admissions et de l’expérience du système universitaire sur la persévérance aux études en enseignement supérieur : perspective de recherche en Afrique Alexis Salvador Loyé, Eric Frenette & Jean-François Kobiané..........................109 Legal Educational Platforms and Disciplines of the Future Cosmas Cheka.....................................................133 ‘Makererization’: Politics, Leadership and Management at the University of Bostwana from 2011–2017 Christian John Makgala....................................147